Colación de Matritensis 3767: Ovidio, Metamorfosis - Pablo Toribio (Exemplaria Classica, 2009)
The author presents the results of a collation of the MS 3767 held in the Spanish National Library. This manuscript, which dates from the 13th century and contains the full text of Ovid´s Metamorphoses, had not been collated before.